Aquinas on humility and relational greatness - Pinsent, A (Routledge, 2020)
Humility is a practically orphaned virtue in contemporary virtue ethics, and its theological associations in classical and medieval texts do not, at first glance, commend humility in a secular world. In response, I examine in this chapter the place accorded to humility in Aquinas’s relational virtue ethics. I begin by showing how the four species of pride he identifies inhibit flourishing from both a first- and second-person perspective, and how Aquinas’s defends both humility as a guardian of relationships and a concomitant virtue of greatness. I conclude by observing how Aquinas’s account of humility also transposes into a more secular framework, given the need for a disposition to protect the many interpersonal relationships and their fruitfulness that are associated with human flourishing.